Simulation des changements climatiques dans Civilization VI Gathering Storm - Vincent Boutonnet; Marco Barroca-Paccard (VertigO, 2022)
Civilization VI Gathering Storm offers important new features, including the effects of fossil fuel consumption on CO2 emissions, the climate changes and the occurrence of natural disasters. The game analysis shows the importance of different types of disasters in a game. The management of disaster risks simulated in the game is carried out according to a technicist perspective since many technologies discovered over the course of a game make it possible to manage disaster risks and maintain the expansion and ownership of the territory. The probability of occurrence and the intensity of certain disasters will also increase with global warming linked to the increase in CO2 emissions from the industrial age. The management of these climate changes can be achieved thanks to the World Congress allowing a temporary ban on the exploitation of certain resources. In general, the game simulates some current environmental issues, but does not completely render a model of sustainable development, because the proposed political and technological solutions rule out the social and ecological impacts of these choices and do not integrate many contemporary environmental issues. These principles of the game can be questionable. However, from a didactic point of view, they can also constitute learning opportunities because the game offers an important playful aspect and offers real freedom of choice of the type of development. The game thus has didactic and educational potential by allowing students to discuss a vision of sustainable development based solely on political and technological control.